Soft power and hard power America and China are a model study in political geography - Dr. Hadi Kaim Jalan Al-Shahmani (Journal of College of Education, 2023)
The research aims to identify the concept of power that characterizes states, and the types of power that influence international relations. The research deals with the concept of hard power, its sources and applications. The research also deals with the concept of soft power. With the complexity of the international system, the overlapping interests of the superpowers, the change in the balance of power, and the emergence of many international and non-international actors on the international scene. The United States of America, which seeks to maximize its profits, has to balance between the use of hard and soft power in order to maintain its weight in the international system, which called for the adoption of smart power in foreign policy as an integrated strategy that seeks to combine hard and soft power and the use of smart To put pressure when necessary, so that the use of smart force is a qualitative addition to the American strengths to achieve its goals in American national security And who tries to take over the military and technological superiority of the United States of America to achieve its goals and interests, regardless of the damage it causes to other countries, but despite the prevalence of the concept of smart power, hard power still affects strongly and effectively on the international arena, especially with the emergence of terrorist organizations such as ( ISIS), against which hard force must be used to deter it from committing crimes against civilians, the elderly and children.
Keywords: powers , USA, China , geopolitics .